Thermo-economic and design analysis of a solar thermal power combined with anaerobic biogas for the air gap membrane distillation process. (1st April 2022) - AL-Arfi, Ismail; Shboul, Bashar; Poggio, Davide; Ingham, Derek; Ma, Lin; Hughes, Kevin; Pourkashanian, Mohamed
Highlights: A new hybrid of solar and biogas system is proposed and modelled in MATLAB Simulink. A thermo-economic assessment of the system has been carried out. Sensitivity analysis is carried out to investigate the effects of design parameters. The total hourly costs lie between 30 $/h and 70 $/h. A theoretical foundation for designing and operating a new hybrid system is developed. Abstract: In this paper, a novel layout of concentrating solar power linked in series with anaerobic digestion is presented to power an Organic Rankine cycle (ORC-Toluene) and Air Gap Membrane Distillation (AGMD) for desalination and electric power generation. The novelty emerges from some facts which are centralized around the use of a hybrid electric generation via Concentrated Solar Power (CSP) and anaerobic digestion biogas to achieve higher stability and profitability. Meanwhile, the cogeneration through the waste heat of the ORC drives the AGMD, which benefits as well from the higher stability due to hybridization. The proposed system has been designed through advanced modeling in the MATLAB/ Simulink® that facilitates the interaction of the individual energy technologies efficiently. To ensure reliability, the anaerobic digestion process has been used as a backup unit to compensate for the absence of solar energy and for the disposal of organic waste. A technical sensitivity analysis has been conducted for all the system units in order to reduce the respective design limits and identify optimum operational windows. The investigations are preformed based on energy, exergy, and cost analyses to produce 100–1500 m 3 /day of freshwater. The results reveal that the total hourly costs are found within the range of 30–70$/h which are considered to be remarkable results when comparisons are made with the conventional desalination processes. The range of total water price, $/m 3 was found to fluctuate between 0.5 and 1.45$/m 3 . The performance of the model has been tested in a rural area in Oman, and a thorough thermo-economic analysis of the integrated system has been conducted.